Novel 1,2,4-triazoles derived from Ibuprofen: synthesis and in vitro evaluation of their mPGES-1 inhibitory and antiproliferative activity - BİNGÖL ÖZAKPINAR, ÖZLEM; KULABAŞ, NECLA; TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY (My University, 2022)
Some novel triazole-bearing ketone and oxime derivatives were synthesized from Ibuprofen. In vitro cytotoxic activities of all synthesized molecules against five cancer lines (human breast cancer MCF-7, human lung cancer A549, human prostate cancer PC-3, human cervix cancer HeLa, and human chronic myelogenous leukemia K562 cell lines) were evaluated by MTT assay. In addition, mouse embryonic fibroblast cells (NIH/3T3) were also evaluated to determine the selectivity. Compounds 18, 36, and 45 were found to be the most cytotoxic, and their IC50 values were in the range of 17.46-68.76 mu M, against the tested cancer cells. According to the results, compounds 7 and 13 demonstrated good anti-inflammatory activity against the microsomal enzyme prostaglandin E2 synthase-1 (mPGES-1) enzyme at IC50 values of 13.6 and 4.95 mu M. The low cytotoxicity and non-mutagenity of these compounds were found interesting. Also, these compounds significantly prevented tube formation in angiogenesis studies. In conclusion, the anti-inflammatory and angiogenesis inhibitory activities of these compounds without toxicity suggested that they may be promising agents in anti-inflammatory treatment and they may be supportive agents for the cancer treatment.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Alkoloidler; Sağlık Bilimleri; Diğer; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Alcaloides; Health Sciences; Other; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); KİMYA, UYGULAMALI; Temel Bilimler (SCI); KİMYA, TIBBİ; KİMYA, MULTİDİSİPLİNER; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, MEDICINAL; CHEMISTRY, MULTIDISCIPLINARY; PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Farmakoloji; İlaç Keşfi; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Fizik Bilimleri; Pharmacy; Pharmacology; Drug Discovery; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Physical Sciences; 1,2,4-Triazole; Atropisomer; Diastereotope; X-ray diffraction; Cancer; Angiogenesis; mPGES-1; Cytotoxicity; PROSTAGLANDIN-E SYNTHASE-1; ANTIINFLAMMATORY ACTIVITY; HYBRIDS SYNTHESIS; BETA-CATENIN; TUMOR-GROWTH; DERIVATIVES; COX-2; DISCOVERY; DESIGN; ANTIBACTERIAL